Low-Frequency Noise and Microplasma Analysis for c-Si Solar Cell Characterization - Jiří Vanek; Jan Dolensky; Zdenek Chobola; Mirek Luňák; Aleš Poruba (International Journal of Photoenergy)
This paper brings the comparison of solar cell conversion efficiency and results from a noise spectroscopy and microplasma presence to evaluate the solar cell technology. Three sets of monocrystalline silicon solar cells (c-Si) varying in front side phosphorus doped emitters were produced by standard screen-printing technique. From the measurements it follows that the noise spectral density related to defects is of 1/f type and its magnitude. It has been established that samples showing low noise feature high-conversion efficiency. The best results were reached for a group solar cells with selective emitter structure prepared by double-phosphorus diffusion process.